Bookseller’s Classification: Classification Examples and Criteria of Croatian Booksellers in Sales Catalogs and Book Lists from the Beginning of the 20th Century (Libellarium: journal for research in the field of information and related sciences, 2012)
The aim of the paper is to conduct research on the topic of ways of bookstore (sales) classification of Croatian bookstores from the beginning of the 20th century. By content analysis of the 17 sales lists/catalogs of books from Dubrovnik, Split, Zadar, Karlovac, Zagreb and Osijek, the classification structure has been reconstructed, and the criteria according to which the booksellers offerings have been classified in the early 20th century have been determined. Conducting of the analysis established the following criteria of the bookstore classification: topic/content, form/type of work, type of corpus, genre, language, purpose, publishing series, publisher, time of publication, (new edition), time of publication/purchase, customer's specific interests, number, letter and author. Order of enumeration within specific categories is mostly alphabetic, numeric or according to order of publication. Unlike the library classification and classification systems in general, the problematics of bookstore classification is not very present in the current existing sources. Research studies that focus on the history of bookselling, even if they reveal ways of classification of booksellers offers remain on a descriptive level without any deeper analysis of the criteria or possible reasons of such classification. Therefore, the contribution of the paper is a detailed analysis of a larger pattern of bookstore sales catalogs, and also an attempt of illuminating the criteria and reasons of creating a system of bookstore classification in the defined historical, spatial and time context.
Keywords: bookstore classification; bookstore sales catalogs; Booksellers & Publishing “Jadran”; Booksellers “Morpurgo”; Croatian Bookshop in Zadar; Bookshop of Vjekoslav Göszl; Bookshop “Zabavna biblioteka”; Bookshop and Stationery “Srećko Hofman”; Antique Shop “Mirko Brayer”; Bookshop “L. Reich”; Bookshop “S. Kugli; Croatian Press Bureau Inc., Osijek Branch